Dual-Polarized Wideband Filtering Antenna Array Based on Stacked-PCB Structure - Matti Kuosmanen; Sten E. Gunnarsson; Johan Malmstrom; Juha Ala-Laurinaho; Jari Holopainen; Ville Viikari (IEEE Open Journal of Antennas and Propagation)
This paper investigates a thin low-pass filtering antenna array based on dual-polarized Vivaldi elements. The low-pass filtering in the antenna elements reduces the requirement for the front-end filtering between the antenna and the microwave electronics, resulting in improved overall out-of-band suppression, size reduction, and lower cost. The array employs a novel stacked-PCB structure, where simple two-sided PCBs are stacked on top of each other. The via-connected metal layers of all PCBs form a tapered slotline along the surface normal of the PCBs. The filtering effect is realized by corrugating the tapered slotlines, which provides effective, space-saving integration of the filters that fit into a half-wavelength lattice. According to unit-cell simulations, the proposed antenna array operates at 6–18.5 GHz, and the stopband extends from 21 GHz to 37 GHz. The antenna array provides a −10-dB active reflection coefficient (ARC) with beam-steering angles within ±60° in E- and D-planes, and −6 dB within ±55° in the H-plane. At stopband frequencies, the attenuation with respect to simulated total efficiency is at least 20 dB. The operation of the proposed antenna array is confirmed by measurements of an $11× 12$ antenna array prototype, which show that the gain suppression level in the stopband is more than 30 dB up to 37 GHz, and more than 20 dB up to 40 GHz.